Punishment or forgiveness? The hard dealing with the dictatorial past in democratic Portugal – The case of the political purges - Rezola, Maria Inácia (2019)
According to the British academic Laurence Whitehead (2002), each country manages differently and finds its own solution to the demands of truth and justice in relation to its dictatorial past during democratization processes. While some chose a “communicative silence”, in others the demands for “hygienic purges” prevails. But whatever the option, another possibility will always remain latent, as desirable. In Portugal, the revolutionary nature of the transition to democracy and the state’s crisis that branded it created a “window of opportunity” for a strong and immediate reaction to the past. Among the different formulas of political justice adopted purges, i.e., the institution of processes through which abusive or corrupt officials are excluded from the public service, stand out. It is our aim to analyse the legislation that framed these purges, considering the transition different stages, and to perceive its impacts and relations with the progress of the Portuguese revolution.